A comparative study on the effectivity of live lecture and audio-visual lecture on the acquisition of basic dental knowledge of kindergarten children - Francisco, Yvette
Two Kindergarten honor section with 30 students each were used. One served as subjects for the live lecture method while the other, for the audiovisual lecture. Before each lecture proper, a pretest was given. Lectures were conducted simultaneously. One section listened to a live lecture while the other listened to a taped lecture together with acetate transparencies shown on the screen. Both lectures lasted for only 8 minutes. A post test was given afterwards. Analysis of results showed that there was no significant difference in the effectivity of the live lecture and audiovisual lecture on the acquisition of basic dental knowledge of Kindergarten children.